The Identity of the Herb Todda–Vaddi in Van Rheede’s Hortus Malabaricus - Daniel, Jisha; Santhoshkumar, Ettickal Sukumaran; Rajendraprasad, Madhavan; Decruse, Sabarimuthan William (Journal of Tropical Life Science, 2021)
The ambiguity on the botanical identity of Todda-vaddi in Rheede’s Hortus Malabaricus is clarified as Biophytum reinwardtii (Zucc.) Klotzsch here. A detailed description, photographs and other relevant notes are provided.